The organizational mechanism of new technology implementation: an empirical study in the Chinese construction industry - Tianjiao Li; Zhiwei Helian; Xiujuan Jin (Journal of Asian Architecture and Building Engineering)
In the past decade or so, an increasing number of construction organizations have shifted from traditional CAD to BIM, which requires organizations to make corresponding changes and can be seen as a progressive organizational change. However, existing research knows little about the organizational management mechanisms for BIM implementation. From the perspective of organizational change, considering the role of transformational leadership and organizational unlearning, this study constructs a framework to explore the organizational mechanism of BIM implementation. Based on empirical analysis of 124 samples from mainland China, it was found that transformational leadership contributes to the improvement of an organization’s BIM implementation level and the pathway is mainly achieved through organizational unlearning. This study contributes to the construction industry’s organizational change and new technology implementation by inferring and validating the positive roles of transformational leadership and organizational unlearning in promoting BIM implementation. Research findings can also provide helpful guidance for industry participants to implement BIM within organizations successfully.